Influences of tool pin profile on the friction stir welding of AA6061 - Emamian, S. (Asian Research Publishing Network, 2016)
AA6061 aluminum alloy is very useful material in the light weight fabrication. Friction stir welding (FSW) is a solid state joining process that is feasible for this material. Appropriate pin profiles and tool design can generate proper heat and mixing the plasticized materials. In this study AA6061-T6 used as a base metal and H13 steel is selected for fabrication of different pin profiles. Four pin profiles used to fabricate joints with different rotation and traverse speed. Obtained results showed that threaded cylindrical produced better joints. Furthermore, increasing the FSW speeds has influence on tensile strength. Â©2006-2016 Asian Research Publishing Network (ARPN).